PENGEMBANGAN MEDIA VIDEO ANIMASI PADA MATA PELAJARAN IPA KELAS V DI UPT SDN NO 69 GALESONG 1 KABUPATEN TAKALAR - Hidayatul Anas; Dedy Aswan; Abdul Hakim (STKIP Subang, 2026)
This development research aims to identify needs, design, and determine the validity and practicality of animated video learning media in Science subjects for fifth-grade students at UPT SDN No. 69 Galesong 1. This research applied the 4D development model by Thiagarajan, which consists of Define, Design, Develop, and Disseminate stages. The subjects involved 30 fifth-grade students during the needs analysis phase, 15 students in small-scale testing, and 1 Science classroom teacher. Data were collected through validation questionnaires and user response sheets. The alpha validation results indicated high validity, with content experts scoring 93.33% (very valid), media experts scoring 93.33% (very valid), and learning experts scoring 88% (valid). The beta practicality testing showed a student response rate of 90.84% (very practical) and a teacher response rate of 97.5% (very practical). These findings indicate that the developed animated video learning media is highly valid, practical, and feasible for enhancing students' interest and conceptual understanding in elementary Science instruction.